YouTube as a Patient Education Resource for Male Hypogonadism and Testosterone Therapy - Christopher J. Warren, BA; John Wisener, BS; Brittany Ward, BS; Sara Behbahani, MS; Tejash Shah, MD; Adam Fano, BS; Boris Paskhover, MD; Hossein Sadeghi-Nejad, MD (Sexual Medicine, 2021)
Introduction: YouTube is an unregulated platform that patients are using to learn about treatment options. Aim: To assess the reliability of YouTube videos (YTVs) related to male hypogonadism and testosterone therapy. Methods: Searching on YouTube by relevance and view count, we analyzed the top 10 videos (80 videos total) for the following search terms: low testosterone, testosterone replacement therapy, AndroGel, and hypogonadism. Main Outcome Measure: We recorded the number of views for each video, evaluated videos using the DISCERN score (DS) criterion, and compared the DS for videos including board-certified physicians and videos without. A second comparison was made between videos with board-certified physicians in urology, endocrinology, other MD, and those without any physician. Results: The YTVs analyzed received a total of 38,549,090 views, a median of 25,201 and 17.30 views/day. Videos that featured physicians had significantly fewer views/day than videos that did not (39.48 CI 9,72 vs 1,731 CI 330, 3,132; P = .019). Most YTVs studied were unreliable. The median DS across all videos was 2. However, most videos created by physicians were found to be reliable with a median DS of 4. In addition, YTVs that did not feature a physician were found to be significantly less reliable than videos that featured a physician (3.22 CI 3.06, 4.09 vs 1.87 CI 1.56, 2.18; P < .001). There was no significant difference in the reliability or viewership of YTVs stratified by physician type. Conclusion: Most YTVs related to male hypogonadism/testosterone therapy were unreliable, but there are reliable YTVs available. Reliable videos usually feature a physician and receive fewer views than unreliable YTVs. Physicians and academic societies should work to provide verified videos to provide patients with reliable information about male hypogonadism and testosterone therapy.CJ Warren, J Wisener, B Ward, et al. YouTube as a Patient Education Resource for Male Hypogonadism and Testosterone Therapy. Sex Med 2021;9:100324.